Evaluation of nutrient canals by intra oral digital radiography technique(sensor) for hypertention patients - بدور سلمان; عمار أمون (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Systemic diseases have shown a clear impact on various body organs and its vital system. One of these diseases is hypertension, which causes serious health problems such as cardiovascular disease, cerebrovascular accidents and kidney diseases. Therefore, it is necessary to study the influence of hypertension on the nutrient canals of the teeth by the technique of digital radiograph, to find out if we can obtain information that may help dentists and specialists to study patients general health or provide more comfortable ways for monitoring and examining. Aims: To find out the extent of the association between the appearance of nutrient canals and the incidence of hypertension, and the possibility of using the radiological technique (sensor) to diagnose hypertension in case there was an association. Materials and Methods: The total number of the sample was 150 patients (75 patients for the control group - 75 patients for the arterial hypertension group). Patients with hypertension were selected from patients visiting the Department of Oral Medicine, Faculty of Dentistry at Tishreen University, and from a dental clinic. A control group of healthy individuals was selected as a comparison group. Blood pressure was measured for all subjects who would be included in the study. The radiographic imaging was done with a digital intraoral imaging technique (sensor) for the frontal area of the lower jaw, then data recording and statistical analysis was performed using the statistical program (SPSS V20) Results: The results showed that there was a statistically significant increase in the rate of the appearance of nutrient canals by 61.3% among hypertensive patients, compared to 30% for the control group. The results also showed that the appearance of nutrient canals was very similar in both sexes and in both groups, and there was no correlation between the appearance of nutrient canals and gender.